2015
DOI: 10.1111/ced.12709
|View full text |Cite
|
Sign up to set email alerts
|

Hypereosinophilic syndrome: an indolent rash with a serious cardiac complication

Abstract: Idiopathic hypereosinophilic syndrome (HES) is a rare disorder, characterized by prominent blood or tissue eosinophilia with ensuing tissue damage, which is diagnosed after exclusion of underlying diseases known to cause HES. Sustained eosinophilia is associated with cardiac disease, including endomyocardial thrombosis and fibrosis, leading to restrictive cardiomyopathy, valvular dysfunction and increased thrombotic tendency. Aneurysmal coronary artery disease (CAD) occurring in the absence of stenotic atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…After removing duplicate and redundant articles, 25 papers were included in the present study for the final review and analysis. A thorough reading of these articles yielded a total of 32 cases of idiopathic HES with cutaneous involvement 5–29. A comprehensive review of these case reports indicated a slight male predominance (male, n = 19; female, n = 13).…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicate and redundant articles, 25 papers were included in the present study for the final review and analysis. A thorough reading of these articles yielded a total of 32 cases of idiopathic HES with cutaneous involvement 5–29. A comprehensive review of these case reports indicated a slight male predominance (male, n = 19; female, n = 13).…”
Section: Discussionmentioning
confidence: 99%